Class-I myosin responds to changes in membrane tension during clathrin-mediated endocytosis in human induced pluripotent stem cells - Samantha L. Smith; Tong Zhan; Wan Li; Henry De Belly; Qing Zhang; Ke Xu; Orion D. Weiner; David G. Drubin (Proceedings of the National Academy of Sciences, 2026)
Clathrin-mediated endocytosis (CME) is an essential cellular process that needs to operate efficiently across a wide range of conditions. Internalization of the endocytic site involves forces generated by membrane-bound proteins and Arp2/3-mediated branched actin filament assembly to bend the plasma membrane from flat to omega-shaped. In mammalian CME, the requirement for a branched actin filament network varies depending on cell type and differences in membrane tension. However, how the actin network adapts to changes in load in order to ensure robustness of this process over a range of membrane tensions is not understood. Here, we combine live-cell imaging and superresolution microscopy of genome-edited human induced pluripotent stem cells to investigate the role of the mammalian class-I myosin, Myosin1E (Myo1E), in load adaptation. Under normal conditions, sites that recruit Myo1E are rare and exhibit slow CME dynamics. However, as membrane tension increases and CME dynamics are slowed globally, Myo1E is recruited to more sites, likely to increase actin assembly and motor activity, resulting in increased force generation to rescue stalled sites and promote internalization. Loss of Myo1E results in increased Arp2/3 complex lifetime at CME sites under normal conditions, and at high membrane tension, these sites fail to recruit as many Arp2/3 molecules. We propose that Myo1E is recruited to CME sites that have stalled due to increased membrane tension, where it helps build a more effective branched actin network by generating force through motor activity and recruiting additional Arp2/3 complexes to rescue stalled sites.